2006
DOI: 10.1074/jbc.m513344200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Priming Kinases Contribute to Differential Regulation of Collapsin Response Mediator Proteins by Glycogen Synthase Kinase-3 in Vivo

Abstract: Collapsin response mediator proteins (CRMPs) are a family of neuron-enriched proteins that regulate neurite outgrowth and growth cone dynamics. Here, we show that Cdk5 phosphorylates CRMP1, CRMP2, and CRMP4, priming for subsequent phosphorylation by GSK3 in vitro. In contrast, DYRK2 phosphorylates and primes CRMP4 only. The Cdk5 and DYRK2 inhibitor purvalanol decreases the phosphorylation of CRMP proteins in neurons, whereas CRMP1 and CRMP2, but not CRMP4, phosphorylation is decreased in Cdk5 ؊/؊ cortices. Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
244
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(255 citation statements)
references
References 37 publications
8
244
3
Order By: Relevance
“…1B). Interestingly, inhibitors of CDK5 (cyclin-dependent kinase-5), the presumed S522 kinase that primes other CRMP2 sites for subsequent GSK3β phosphorylation (25), did not decrease CRMP2-p-T514, suggesting that lithium decreases CRMP2-p-S522 independently of CDK5 in human neurons (SI Appendix, Fig. S9C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Interestingly, inhibitors of CDK5 (cyclin-dependent kinase-5), the presumed S522 kinase that primes other CRMP2 sites for subsequent GSK3β phosphorylation (25), did not decrease CRMP2-p-T514, suggesting that lithium decreases CRMP2-p-S522 independently of CDK5 in human neurons (SI Appendix, Fig. S9C).…”
Section: Resultsmentioning
confidence: 99%
“…However, phosphorylation of CRMP2-T514 (as well as of CRMP2-S518 and CRMP2-T509) must first be primed by phosphorylation at CRMP2-S522. Phosphorylation of CRMP2 by kinases is balanced by its dephosphorylation by phosphatases (24)(25)(26) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon the established important role of phosphorylation in modulating CRMP-2's activity and interaction with partners proteins, we hypothesized that phosphorylation may also affect its modulation of CaV2.2. Here, we focused solely on evaluating the effect of Cdk5-phosphoryalted CRMP-2 on CaV2.2 because (i) Cdk5 is an obligatory priming kinase [28], (ii) Cdk5-phosphorylated CRMP-2 (at Ser-522) has reduced interaction with partner proteins tubulin and numb [24], (iii) Cdk5-phosphorylated CRMP-2 leads to altered neuronal functionality manifested as a halt in neurite growth [29], and (iv) the Cdk5-phosphorylation site is near the CBD3 binding site on CRMP-2 that is important for its interaction with CaV2.2. Our results show that mutation of the Cdk5-phosphorylation site, but not the RhoK phosphorylation site, regulates CRMP-2-mediated enhancement of Ca 2+ influx.…”
Section: Introductionmentioning
confidence: 99%
“…CRMP2 regulates multiple processes in neurons and was initially discovered to regulate mechanisms of neuronal polarity (9,10). CRMP2 phosphorylation by cyclin-dependent kinase 5 (Cdk5) (11), glycogen synthase kinase 3β (10), Rho-associated protein kinase (12), or the Src-family kinases Fyn (13) and Yes (14) drives its diverse cellular functions, including neurite outgrowth, endocytosis, and ion-channel trafficking (8,(15)(16)(17). Studies of CRMP2 trafficking functions have revealed that CRMP2 facilitates endocytosis of L1-cell adhesion molecule by interacting with the endocytic protein Numb (18) that recruits epidermal growth factor receptor pathway substrate 15 (Eps15), an initiator of clathrin-mediated endocytosis (19).…”
mentioning
confidence: 99%